2014
DOI: 10.1038/eye.2013.305
|View full text |Cite
|
Sign up to set email alerts
|

Early surgery for epiretinal membrane preserves more vision for patients

Abstract: Purpose To establish whether early vitrectomy for epiretinal membrane (ERM) is preferable to delayed surgery. Methods We carried out a retrospective study of 120 eyes from 120 patients with preoperative visual acuity (VA) of 6/60 or better. Pre-operative logMAR score was considered to act as an appropriate proxy measure for time of surgical procedure, with scores of 0.3 or less considered to represent early surgery, scores of 0.4 or 0.5 considered to represent medium surgery, and scores of 0.6 or more consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 5 publications
4
34
0
Order By: Relevance
“…). Distortion and blurring, especially under low contrast conditions, may not be fully reflected with VA testing (Rahman & Stephenson ). Other aspects of the visual function may add valuable information to that obtained by BCVA assessment, as it represents acuity in the central 1° of visual field (Das et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). Distortion and blurring, especially under low contrast conditions, may not be fully reflected with VA testing (Rahman & Stephenson ). Other aspects of the visual function may add valuable information to that obtained by BCVA assessment, as it represents acuity in the central 1° of visual field (Das et al.…”
Section: Discussionmentioning
confidence: 99%
“…Metamorphopsia significantly correlates with a patient's vision-related quality of life, as was previously demonstrated by the 25-item National Eye Institute Visual Function Questionnaire and a simple 10-question metamorphopsia questionnaire (Fukuda et al 2009;Arimura et al 2011). Distortion and blurring, especially under low contrast conditions, may not be fully reflected with VA testing (Rahman & Stephenson 2014). Other aspects of the visual function may add valuable information to that obtained by BCVA assessment, as it represents acuity in the central 1°of visual field (Das et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported good surgical outcomes and many prognostic factors, such as preoperative visual acuity, retinal thickness, photoreceptor layer status, and the status of other specific layers of the retina, for the outcome following ERM surgery [13,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. Among these, preoperative vision is a well-known prognostic factor that influences postoperative vision.…”
Section: Discussionmentioning
confidence: 99%
“…2 Wang et al suggested in their case report that even in cases of UES with localised subretinal fluid, a surgical intervention with sclerotomies performed in all four quadrants may be necessary to successfully manage the patient.…”
Section: Sir Reply To: 'Four Quadrant Sclerotomies For Uveal Effusiomentioning
confidence: 99%